(untitled) (Research, Society and Development, 2021)
Currently, woman are still stigmatized in the sports field. Mainly, in what refers to the practice of Fighting, Martial Arts and Combat Sports (AM&EC). In the school context, scientific studies dealing with the interface between struggles and gender issues are scarce. This investigation sought to point out the meaning of student about female participation in classes of Struggles in Physical Education. The students of the 3rd year of high school answered a semi-structured questionnaire, before and after being submitted to six meetings that involved theoretical classes and subsequent practical classes, totaling 140 minutes, each meeting. The study took place at the Dom Ungarelli Educational Center, in Pinheiro-MA, in the classroom adapted with fighting mat and covered 13 modalities of Fights. The parents authorized us to participate, by signing the Free and Informed Consent Form (TCLE), excluding those who did not attend 75% of the class or did not answer the questionnaire. The results show that, preliminary, of the 150 students who participated in the study, 120 considered negative the participation of girls, because of the risk of getting hurt; only 19 judged them capable and 11 with equal rights to boys. Subsequently, all approved them in Fighting classes, 35 confirmed their capacity and 60 students began to recognize it as a practice in which girls also have right to participate; and we emphasize that 55 students acknowledge that the Struggles break the gender prejudice. Therefore, we conclude that the content Fighting/Martial Arts/Combat Sports can be an important educational tool in combating stereotypes and prejudices.